Предмет: Алгебра, автор: hovanskaya2008

докажите тождество (а^2 + в^2 - с^2) - ( в^2 + с^2 - а^2) + ( с^2 - а^2) = а^2 - с^2

Ответы

Автор ответа: RewMath
2

(а^2 + в^2 - с^2) - (в^2 + с^2 - а^2) + (с^2 -а^2)= а^2 - с^2

Левая часть:

(а^2 + в^2 - с^2) - (в^2 + с^2 - а^2) + (с^2 -а^2) = а^2 + в^2 - с^2 - в^2 - с^2 -(-а^2) + с^2 - а^2 = а^2 + в^2 - с^2 -в^2 - с^2 + а^2 + с^2 - а^2 = а^2 - с ^2

Правая часть:

а^2 - с^2

Тождество верно

Похожие вопросы
Предмет: Математика, автор: vladhacker
Предмет: Математика, автор: Princess51911